Field study indicating susceptibility differences between salmonid species and their lineages to proliferative kidney disease. Issue 10 (1st August 2020) - Syrová, Eva; Palíková, Miroslava; Mendel, Jan; Seidlová, Veronika; Papežíková, Ivana; Schmidt‐Posthaus, Heike; Somerlíková, Kristina; Minářová, Hana; Mareš, Lukáš; Mikulíková, Ivana; Pikula, Jiří; Mareš, Jan
Abstract: Tetracapsuloides bryosalmonae (Myxozoa: Malacosporea) is the causative agent of proliferative kidney disease (PKD), which affects both wild and farmed salmonid fish. The objective of this study was to outline differences in susceptibility to PKD in different salmonid species, hybrids and breeding lineages. Susceptibility to T. bryosalmonae infection was established based on cumulative mortality, pathological findings and detection of T. bryosalmonae in the kidney using immunohistochemistry and molecular methods. Determination of pure and hybrid individuals of different species in the genus Salvelinus, and dissimilarity of rainbow trout lineages, was performed using traditional polymerase chain reaction (PCR) and microsatellite analyses. Rainbow trout displayed higher disease severity compared with brook trout and Alsatian charr. Moreover, the results indicated differences in infection susceptibility, not only among different salmonid species but also among different lineages of charr and rainbow trout. Our study indicated that some salmonid species and even different lineages of the same species are more suitable for farming under PKD pressure.